Case reportAdenomyosis in a patient with mosaic Turner syndrome: case report - Kojima, Rieko; Nakagawa, Koji; Ohgi, Shirei; Horikawa, Takashi; Kawachiya, Satoshi; Saito, Hidekazu (Archives of Medical Science, 2008)
Adenomyosis has only been reported in one patient with mosaic Turner syndrome. We report a case of mosaic Turner syndrome in a patient who suffered from hypermenorrhoea and severe anaemia due to adenomyosis. A 40-year-old woman visited us desiring to conceive. The patient had got pregnant twice, but they resulted in spontaneous abortion. After her third miscarriage, chromosomal banding was performed and the patient was found to have a mosaic chromosome complement (45,X [9]/46,XX [21]). We report an extremely rare case of a patient with mosaic Turner syndrome who presented with typical clinical symptoms of adenomyosis.